Dependence of the photosynthesis quantum yield in oceans on environmental factors - Bogdan Woźniak; Jerzy Dera; Dariusz Ficek; Mirosława Ostrowska; Roman Majchrowski (Oceanologia, 2002)
Statistical relationships between the quantum yield of photosynthesisand selected environmental factors in the ocean have been studied.The underwater irradiance, nutrient content, water temperature andwater trophicity (i.e. the surface concentration of chlorophyllCa(0)) have been considered, utilizing a large empirical data base.On the basis of these relationships, a mathematical model of thequantum yield was worked out in which the quantum yield Phi is expressedas a product of the theoretical maximum quantum yield PhiMAX = 0.125 atom C quanta -1 and six dimensionless factors. Each of thesefactors fi appears to be, to a sufficiently good approximation, dependenton one or two environmental factors and optical depth at most. The modelmakes it possible to determine the quantum yield from known valuesof these environmental factors. Empirical verification of the modelyielded a positive result - the statistical error of the approximatevalues of the quantum yield Phi is 42%.